Urban Heritage and the Contention between Tradition, Avant-garde, and Kitsch: Amman’s Rising “Kitsch Syndromes” and its Creeping Vernacularized Urban Landscapes - Daher, Rami (Ethnologies, 2013)
This article investigates the emergence of certain trends in Amman. It centres on the rise of replications of “historicized” architectural styles or/and the re-invention of the forms of cultural and heritage icons in places that have undergone urban and economic planning and regeneration schemes, projects such as Rainbow Street and Faisal Plaza in Amman. It focuses more specifically on presenting Amman’s urban heritage as an in-between situation where discursive practices lead to an urban reality that has not been recognized, appreciated, properly studied or even incorporated in the formal and popular definitions of Jordan.